(untitled) (Bangladesh Journal of Botany, 2012)
Submontance forest at five different altitudes along the western slope of Frasers’ Research Centre (FHRC) in Raub District, Pahang State of Malaysia by Ward Linkage Method (WLM) was classified. Five plots were set at 1000 m (P1), 1050 m (P2), 1100 m (P3), 1150 m (P4) and 1200 m (P5), and all the trees with diameter at breast height (DBH) ≥ 5 cm have been measured. Cluster analysis by WLM of these plots resulted in the identification of four forest zones (FZ) denoted by FZ1P1, FZ2P2, FZ3P3P4 and FZ4P5. These forest zones were denoted by three most dominant species in term of importance value (Iv) such as Dacrydium elatum (Roxb.) Wall. ex Hook.- Prunus arborea (Blume) Kalkman - Adinandra dumosa Jack (Zone FZ1P1), Trigonobalanus verticillata Forman - Syzygium stapfianum (King) I.M. Turner - Syzygium subdecussatum (Wall. ex Duthie) I.M. Turner (Zone FZ2P2), Syzygium leptostemon (Korth.) Merr. & L.M. Perry - Wikstroemia polyantha Merr - Syzygium napiforme (Koord. & Valeton) Merr. & L.M. Perry (Zone FZ3P3P4) and Syzygium filiforme (Wall. ex Duthie) P. Chantaranothai & J. Parn.- Decaspermum parviflorum (Lam.) A.J. Scott - Litsea machilifolia Gamble (Zones FZ4P5). Correlation analysis showed that the number of trees in 0.1 ha, density/ha, DBH, mean DBH, number of species, number of family, number of genus, basal area (BA), mean BA, R, H and E and species with the biggest DBH decreased with increasing altitude. The r-values obtained for these 13 attributes were from – 0.13 to – 0.99. The distribution of trees were found to differ between DBH Class (DBHC) in all FZ. This study revealed that 73.1 to 88.17% of trees in all FZ fall into DBHC1 and DBHC2. On the other hand, 1.02 to 6.28% fall into DBHC5, DBHC6 and DBHC7. The distribution of species was different between Iv Class (IvC) all the four FZ. It was found that from 77.68 to 93.75% of the species fall into IvC1 and IvC2, and between 1.66 to 5.12% of the species fall into IvC4 and IvC5. Key words: Cluster analysis; Submontane forest; Western slope; Malaysia DOI: http://dx.doi.org/10.3329/bjb.v40i2.9767 Bangladesh J. Bot. 40(2): 121-132, 2011 (December)